Social networking use, mental health, and quality of life of Hong Kong adolescents during the COVID-19 pandemic - Yu, Lu; Du, Meng (Frontiers in Public Health, 2022)
During the COVID-19 pandemic, adolescents’ use of social networking sites/apps (SNSs) has surged, and their mental health and quality of life have also been significantly affected by the pandemic and its associated social-protection measures. The present study first examined the prevalence of SNSs use and social networking addiction (SNA), the mental health status, and the health-related quality of life among Hong Kong adolescent students (N = 1,147; age = 15.20 ± 0.53 years) from 12 randomly selected local secondary schools. We further investigated the associations of the youths’ daily use of SNSs and their SNA with their mental health and quality of life during the pandemic. Results showed that 46.4% of the participants reported using SNSs often or very often, and 7.8% met the criteria for SNA using Bergen’s Social Media Addiction Scale. The prevalence of mild to extremely severe depression, anxiety, and stress among the adolescents stood at 39.6%, 37.5%, 48.8%, respectively, and the participants’ physical, social, and school functioning were lower than the norms of healthy adolescents before the pandemic. Participants who used SNSs but for less than 3 hours per day (excluding students who never used SNSs) showed significantly fewer problems of depression, anxiety, and stress than did those who spent more than 3 hours per day on SNSs. Social networking addiction was found to be consistently associated with poor mental health and health-related quality of life. This study points to the need to provide extra support to promote the well-being of young people, especially those in disadvantaged situations (e.g., non-intact family), and it supports the potential protective effect of guiding adolescents to use SNSs appropriately in order to mitigate their negative emotions during contexts such as that of the pandemic.